Negotiating Digital Polygamy: Hadith, Authority, and Public Engagement on Instagram - Billah, Rodina; Mukhammad Zamzami; Abd A’la (Journal of Islamic Philosophy and Contemporary Thought, 2025)
Polygamy remains a controversial issue in contemporary Islamic discourse, causing tension between the legitimacy of hadith texts and their social implications for gender justice. This study explores the construction of discourse on polygamy in the digital space through a netnographic approach to the Instagram account @khalidbasalamahofficial. The analysis focuses on the representation of hadiths on justice in polygamy and how the public responds to, affirms, or criticizes the content of these sermons. The results show that hadiths are selectively represented to affirm the legality of polygamy in Islamic law, while also functioning as a symbolic instrument in building digital religious authority. However, public interactions give rise to negotiations of meaning that indicate an epistemic transformation, in which religious authority shifts from formal institutions to a more participatory digital public sphere. In this context, the Qirā’ah Mubādalah approach offers a reinterpretative framework that emphasizes the principles of reciprocity and justice, demanding the realization of equal social relations and fair and dignified treatment of women. Thus, polygamy is not only understood as a permissible practice but also as an arena for moral reflection, affirming that balance, equality, and mutual benefit are at the core of religious authority and practice in the digital age.